Five go to smuggler's top - Blyton, Enid (Hodder Children's Books London, 2012)
"Are there still smugglers at Smuggler's Top? The Famous Five go to stay at the large old house and discover secret hiding places and underground tunnels! Then they catch people signalling out to sea - who can these smugglers be? Can Julian, Anne, Dick, George and Timmy the dog discover the answer?"--Publisher